Enhancing surgical precision and efficiency: a study and comparison of a three-dimensional surgical video system in proliferative diabetic retinopathy surgery - Zhang, Xiang; Zhu, Danni; Li, Wenbo; Hu, Hanling; Nie, Zetong; Guo, Haoxin; Wang, Zhaoxiong; Li, Xiaorong; Hu, Bojie (Frontiers in Medicine, 2023)
Abstract Purpose: To investigate the safety and efficacy of three-dimensional (3D) surgical video systems for proliferative diabetic retinopathy (PDR). Methods: This retrospective clinical case study included 30 patients (30 eyes) with proliferative diabetic retinopathy (PDR). Patients were divided into two groups: one underwent surgery using a 3D surgical video system (14 cases, 14 eyes), while the other had traditional microscope surgery (16 cases, 16 eyes). Safety and efficacy were assessed through predetermined surgical parameters, including surgical duration, intraoperative membrane removal rate, and occurrences during intraoperative and postoperative phases. Results: Our study revealed noteworthy differences in various aspects between the 3D surgical video system group and the traditional microscope surgery group. Specifically, the mean surgical time was 30.25±14.43 minutes in the 3D surgical video system group, compared to 38.56±18.71 minutes in the traditional microscope surgery group (p=0.051). Furthermore, the mean membrane removal time was significantly shorter in the 3D group at 2.53±1.52 minutes, as compared to 3.23±1.76 minutes in the traditional group (p=0.042). Importantly, the membrane removal rate also displayed a significant difference, with the 3D group at 0.55±0.07 and the traditional group at 0.41±0.11 (p=0.018). However, no notable differences were observed between the two groups in terms of intraoperative and postoperative incidence. Conclusion: The safety and efficacy obtained via the 3D surgical video system in PDR surgery were comparable to that via traditional microscopic surgery.